The relationships between perfectionism, anxiety and depression across time in paediatric eating disorders. (August 2019) - Morgan-Lowes, Katherine L.; Clarke, Patrick J.F.; Hoiles, Kimberley J.; Shu, Chloe Y.; Watson, Hunna J.; Dunlop, Patrick D.; Egan, Sarah J.
Abstract: Objective: The aim was to examine in children and adolescents with eating disorders the relationship between perfectionism, anxiety, and depression at intake assessment and whether intake perfectionism was significantly associated with anxiety and depression at 6 months and 12 months post-intake review. Method: Participants were 167 females aged 10–17 years ( M = 14.6, SD = 1.20) with a diagnosis of an eating disorder, who were assessed at intake to an eating disorders treatment program to receive either inpatient, day or outpatient care. Participants were re-assessed at 6 and 12 months post-intake review. Results: At intake and 6 and 12 months post intake review perfectionism had a significant positive correlation with anxiety and depression. Perfectionism did not however determine change in anxiety and depression over time at 6 and 12 months post-intake review. Conclusions: Despite perfectionism being significantly associated with anxiety and depression, further research is required to explore the relationships between perfectionism, anxiety and depression over time. Highlights: Perfectionism was significantly associated with anxiety and depression Perfectionism did not account for how anxiety changed over time at 6 and 12 months post-intake review Perfectionism did not account for how depression changed over time at 6 and 12 months post-intake review